PENDAMPINGAN PRAKTIK RASHDUL KIBLAT DI MUSHALLA AL-ANWAR DESA LERANWETAN KECAMATAN PALANG KABUPATEN TUBAN - Faizah, Isniyatin; Lisaniyah, Fashi Hatul; Kamelya, Silvana; Sucipto, Yogi; Putra, Evendi (CV. Kalimasada Group, 2025)
The Rashdul Kiblat practice assistance program at the Al-Anwar Mushalla in Leranwetan Village, Palang Subdistrict, Tuban Regency aims to improve the community's understanding and skills in determining the correct Qibla direction according to the Rashdul Kiblat method. This program is implemented through a series of activities, including socialization, practical training, and direct assistance at the mushalla. Using a participatory approach, residents are provided with knowledge about the importance of accurate Qibla direction in worship, and are trained to use the Rashdul Kiblat method with simple tools that are easy to practice. The expected outcome of this activity is an increased understanding and accuracy in determining the Qibla direction within the community, as well as empowering residents to independently apply and teach this knowledge. This program also aims to strengthen social ties within the community and ensure the sustainability of the practices that have been applied. Overall, this activity has a significant positive impact on the quality of the community’s worship and independence in determining the Qibla direction accurately and precisely.